Portable electrochemical detection of bisphenol A and triclosan using CheapStat and screen-printed electrodes - Soriano, Ron Andrei E.
Endocrine-disrupting compounds (EDCs) are harmful substances that interfere with hormones and can be found in everyday products such as food, drugs, personal care products, and pesticides can eventually end up pollution bodies of water. In particular, the presence of bisphenol A and triclosan have often been mentioned endocrine-disrupting compounds in the environment. There have been studies for the electrochemical detection of these compounds, but none so far used low-cost portable potentiostats to control the electrochemical experiments such as CheapStat. In this study, the electrochemical detection of bisphenol A and triclosan is investigated using CheapStat with screen-printed carbon and screen-printed gold electrodes by varying parameters such as supporting electrolyte concentration, scan rate, and analyte concentration. The study shows that bispenol A and triclosan have been tested to respond to up to 2.5 mM using screen-printed carbon electrode. However, bisphenol A showed no response in screen-printed gold electrodes while triclosan showed worse response when compared to screen-printed carbon electrodes. Two distinct peaks corresponding to each compound were observed when both bisphenol A and triclosan are present. Least squares fitting was used to fit the gathered data to a model for the simultaneous detection. It has been shown in the study that electrochemical detection using the low-cost and portable device CheapStat with disposable screen-printed electrodes is technically feasible.